2020
DOI: 10.3390/tropicalmed5010013
|View full text |Cite
|
Sign up to set email alerts
|

Further Evidence of Inadequate Quality in Lateral Flow Devices Commercially Offered for the Diagnosis of Rabies

Abstract: As a neglected zoonotic disease, rabies causes approximately 5.9 × 104 human deaths annually, primarily affecting low- and middle-income countries in Asia and Africa. In those regions, insufficient surveillance is hampering adequate medical intervention and is driving the vicious cycle of neglect. Where resources to provide laboratory disease confirmation are limited, there is a need for user-friendly and low-cost reliable diagnostic tools that do not rely on specialized laboratory facilities. Lateral flow dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
34
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 29 publications
4
34
1
Order By: Relevance
“…Thus, no fatal outcome in human was reported due to false negative results of the rapid test in Bhutan. Like in our study, many studies [18,26] have reported high specificity (98.9 to 100%) of the rapid test (BioNote), so the false positive outcomes were low which would otherwise may lead to unnecessary use of limited resources including PEP and response activities [26]. However, to our knowledge, only one study has reported false positive results (two false positive among 30 FAT negative specimens), with a specificity of 93.3% [16].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Thus, no fatal outcome in human was reported due to false negative results of the rapid test in Bhutan. Like in our study, many studies [18,26] have reported high specificity (98.9 to 100%) of the rapid test (BioNote), so the false positive outcomes were low which would otherwise may lead to unnecessary use of limited resources including PEP and response activities [26]. However, to our knowledge, only one study has reported false positive results (two false positive among 30 FAT negative specimens), with a specificity of 93.3% [16].…”
Section: Discussionsupporting
confidence: 68%
“…Other studies have also evaluated the rapid kit BioNote, Inc. (Hwaseong-si, Korea) relative to the FAT for detecting rabies virus in the brain samples and have reported diagnostic sensitivities either higher (95 to 100%) [15][16][17][18][19][20][21] or lower (88.3 to 91.7%) [22][23][24] while most of the diagnostic specificities were also between 98.9 to 100% [18]. However, two studies [25,26] detected poor sensitivity of the existing commercially available rapid kits when compared with FAT and the molecular test, but the sensitivity of rapid kit (BioNote) was higher (62-100%) than the other commercially available rapid test kits. The Rapid kit produced by the BioNote target the N-gene (nucleoprotein) while other kits do not have information on which antigen it is targeted and thus may be related to poor sensitivities [22,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, no fatal outcome in human was reported due to false negative results of the rapid test in Bhutan. Like in our study, many studies [18,26] have reported high specificity (98.9 to 100%) of the rapid test (BioNote), so the false positive outcomes were low which would otherwise may lead to unnecessary use of limited resources including PEP and response activities [26]. However, one study has reported false positive results (two false positive among 30 FAT negative specimens), with a specificity of 93.3% [16].…”
Section: Discussionsupporting
confidence: 66%
“…to 100% [18]. However, two studies [25,26] In Bhutan, FAT is the only reference standard test available for diagnosis of rabies and is a routine diagnostic test for rabies recommended both by WHO and OIE [13]. Although FAT is highly sensitive and specific (between 98% and 100%) it depends heavily on the quality of the immunofluorescent conjugate, the maintenance of the fluorescent microscope and on an experienced technician performing test and reading the microscope slides [13].…”
Section: Discussionmentioning
confidence: 99%